THE INFLUENCE OF WORK DISCIPLINE AND EMPLOYEE COMPETENCY ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE - Salbaiti; Muh. Yusuf Qamaruddin; A. Nadirah; Junaidi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Increasing organizational performance cannot be separated from employee compliance with the regulations and norms that apply within the organization. Apart from that, the ability of employees to provide all the capacities and competencies they have can increase motivation and will also increase positive behavior by increasing employee performance which is beneficial for the organization. This research aims to see how work discipline and employee competence influence employee performance through employee work motivation in employees of the East Luwu Timur Regional Revenue Agency. This research is a quantitative study with a population of 102 people, where the sample was determined using saturated sampling, which means the entire population was sampled. Data collection uses a questionnaire that has been tested using validity and reliability tests. The data that has been collected will be carried out descriptive tests and hypothesis testing using the help of the SmartPLS statistical tool. The research results show that work discipline and employee competence have a positive and significant influence on employee performance. Apart from that, work motivation has been proven to act as an intervening variable that strengthens the influence of work discipline and employee competence on employee performance. Specifically, work discipline and employee competency each have a significant direct influence on work motivation, which then influences employee performance. This research underlines the importance of improving work discipline and employee competence as an effort to improve employee performance. Apart from that, increasing work motivation must also be a focus to maximize the potential influence of discipline and competence on employee performance.